2019
DOI: 10.30935/cet.634168
|View full text |Cite
|
Sign up to set email alerts
|

The Experiences of Pre-service Science Teachers in Educational Content Development Using Web 2.0 Tools

Abstract: The present study aimed to improve the experiences of pre-service science teachers in content development using Web 2.0 tools and to determine the effects of these experiences on their self-efficacy beliefs in content development via Web 2.0 tools. The present study was conducted with a mixed design that included empirical and phenomenological methods. Forty-two pre-service science teachers participated in the study. During the implementation, pre-service teachers developed content using Web 2.0 tools such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 22 publications
0
15
0
2
Order By: Relevance
“…After the four phases of selecting the eligible articles for review, 45 were found to be suitable to be used in this systematic review due to the nature of the respective studies. From the articles, four main aspects of teachers' perspectives on the use of Quizizz could be seen, mainly, effectiveness , feasibility [14,15,19,20,22,23,26,27,31,36,38,41,[43][44][45][46][47][48], difficulty [16,17,19,26,28,31,39,41,43,46,[48][49][50][51][52], and motivation [14,17,[24][25][26]31,32,35,38,40,41,44,45,47,49,50,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the four phases of selecting the eligible articles for review, 45 were found to be suitable to be used in this systematic review due to the nature of the respective studies. From the articles, four main aspects of teachers' perspectives on the use of Quizizz could be seen, mainly, effectiveness , feasibility [14,15,19,20,22,23,26,27,31,36,38,41,[43][44][45][46][47][48], difficulty [16,17,19,26,28,31,39,41,43,46,[48][49][50][51][52], and motivation [14,17,[24][25][26]31,32,35,38,40,41,44,45,47,49,50,…”
Section: Resultsmentioning
confidence: 99%
“…This represents a vast majority of the research articles found, and after reading through the 29 articles, it is safe to say that teachers mostly agree that the platform is effective in the classroom. Teachers from various countries agreed that Quizizz is effective in many ways, especially in helping learners to learn in a fun, interactive, and meaningful environment [15,19,20,24,25]. Quizizz has a high potential to be exploited in a myriad of ways, including for assessment and classroom exercises [29,31,32,37,38].…”
Section: Teachers' Perspective On the Effectiveness Of Quizizzmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference between the traditional learning environment and the participatory learning environment In this regard, many studies have addressed the importance of using web tools in a participatory learning environment, including Onbasili (2020), Zainol and Almukadi (2020), Gursoy andGoksun (2019), andWang andHwang (2012) confirmed the effectiveness of using Web 0 tools. 2 in participatory e-learning environments, and its importance in facilitating the process of information exchange and sharing, in addition to its distinctiveness in interactivity and flexibility that would transfer education to learning, and make the learner a receiver, sender, interactive and participant, not just a future and a passive recipient.…”
Section: Figmentioning
confidence: 99%
“…Eğitim faaliyetlerinde üst düzey teknolojilerden yararlanabilen öğretmenler, teknoloji entegrasyonu sürecinin başarısı için oldukça önemlidir (Gürsoy & Göksun, 2019). Maalesef günümüzde sınıfların birçoğu akıllı tahta ve projeksiyon gibi teknolojik cihazlarla donatılmış olsa da birçok öğretmen, öğrenme sürecini kolaylaştırmak için yalnızca PowerPoint sunumlarından faydalanmaktadır (Lee vd., 2019).…”
Section: Introductionunclassified